Infectious Forest Diseases - Gonthier, Paolo (CABI, 2014)
Forest pathology combines fields as diverse as botany, plant physiology, microbiology, clima- tology, soil science, forestry and ecology, but was born an applied science. As a multidiscipli- nary science with an inevitable applied component, forest pathology not only needs to keep up with the advances made in each field, but is also required to answer the needs of a modern and changing society, whose concept of ecosystem services provided by forests has broadened to encompass not only timber production, but also hydrogeological protection, biodiversity, rec- reational use and the preservation of home environments for native people the world over. The development and the extensive use of new analytical approaches, including molecu- lar methods and techniques based in geographic information systems (GIS), has rapidly advanced the knowledge on the infection biology and epidemiology of forest pathogens. These approaches have led to the accelerated discovery of emergent diseases, caused both by known and novel pathogen species. They have helped to clarify the taxonomy of many microbes and their associations with hosts, and have provided much insight into the epidemiology of many diseases, both newly discovered and long known, but poorly understood. A thorough know- ledge of the biology of pathogens and of the epidemiology of any disease remains pivotal in the design of modern, effective, and sustainable control strategies, including integrated disease management programmes. This book aims to provide a review of the most serious infectious diseases in both forest and urban environments, and in landscape settings, and provides practical guidelines for their management based upon both basic and applied scientific research. It was conceived as a com- prehensive reference manual for biotic forest diseases, dealing not only with the better known fungal and fungal-like pathogens, but also with viruses, phytoplasmas, bacteria, higher para- sitic plants and nematodes. My co-editor, colleague and friend Giovanni Nicolotti passed away before reading the chapters that make up this book. He was proud of this ambitious project and this book is dedi- cated to him. I am grateful to all contributors and authors who have made the book possible. I would also like to acknowledge several people who have been of invaluable assistance dur- ing the preparation of this book: Matteo Garbelotto and Michael J. Wingfield, for exciting and useful discussions on the project; Steve Woodward for writing an insightful foreword; and Luana Giordano, whose competent and patient editorial effort has been instrumental at all stages of the preparation of the book.